Instagram As Medium of Promoting English Speaking Skill: English Edupreneurship - Pramudana Ihsan; Eryna Rista Aulia (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2020)
Public speaking has become an integral part of many professions and is at the center of career development opportunities. Therefore, the change in the education system from offline to online has led to new ideas in the implementation of public speaking learning, namely by using Instagram as a learning medium for collecting assignments intended to introduce or sell English language skills which are usually called Edupreneurship. That way, it is hoped that not only carry out learning and collect assignments but also something is obtained. However, learning still prioritizes output. Therefore, in this study, we refer to the personal branding theory. The purpose of this study is to determine how effective the use of Instagram is as a medium to promote English speaking skills, to find out the followers' responses regarding the skills possessed by English students, and also what was gained from promoting English speaking skills. The subjects in this study were students in the 5th semester. The number of respondents was 25 students. This research was conducted using data collection methods through Google forms. The results showed that Instagram provided effects and benefits to students, most of them stated that: (1) Students felt more confident in speaking English, (2) Students felt an improvement in their abilities, (3) Students felt more enthusiastic about positive comments and motivated by negative comments, (4) Students feel that Instagram is the right medium for promoting English speaking skills, (5) Students get input in the form of work.